Metformin reduces the risk of cancer in patients with type 2 diabetes: An analysis based on the Korean National Diabetes Program Cohort. Issue 8 (February 2018) - Kim, Hae Jin; Lee, SooJin; Chun, Ki Hong; Jeon, Ja Young; Han, Seung Jin; Kim, Dae Jung; Kim, Young Seol; Woo, Jeong-Taek; Nam, Moon-Suk; Baik, Sei Hyun; Ahn, Kyu Jeung; Lee, Kwan Woo
Abstract : Abstract: The epidemiological literature suggests that insulin resistance, hyperinsulinemia, and increased levels of insulin-like growth factors place patients with type 2 diabetes mellitus (T2DM) at greater risk of cancer. The association between cancer incidence and the use of antidiabetic medications in patients with T2DM has been recently examined. There have been conflicting reports regarding an association between metformin and cancer risk. The aim of this study was to investigate the relationship between metformin use and the incidence of cancer in Koreans with T2DM. Data from The Korean National Diabetes Program (KNDP, 2006–2014), a nationwide, large-scale, prospective, multicenter cohort study in Korea, were used to study patients with T2DM. Patients ≥30 years old whose complete medical records were available were included in this study. Patients with a history of any cancer on KNDP registration or those who had been diagnosed with any type of cancer within 1 year of metformin use were excluded. Survival curves with respect to the incidence of cancer were plotted using the Kaplan–Meier method. Hazard ratios and 95% confidence intervals for cancer were estimated in a Cox proportional hazards regression analysis. During a mean 5.8 years of follow-up, 164 of the 1918 study patients (335 metformin nonusers and 1583 metformin users) developed cancer. The incidence per 1000 person-years was 21.8 in metformin nonusers and 13.2 in metformin users. Metformin users had a reduced risk of cancer, even after adjustment for demographic characteristics, metabolic parameters, diabetic complications, and other antidiabetic medications (hazard ratio 0.513, 95% confidence interval 0.318–0.826, P = . 0060). Subgroup analysis of metformin users showed a reduced risk of cancer in males, patients < 65 years of age, patients with a T2DM duration < 5 years, nonobese patients, nonsmokers, and good glycemic control group. This large-scale, prospective, multicenter cohort study demonstrated an association between metformin use and reduced cancer risk in patients with T2DM. Abstract : Supplemental Digital Content is available in the text